THE EFFECTIVENESS OF RHYTHMIC GYMNASTICS IN IMPROVING CHILDREN'S GROSS MOTOR ABILITIES - Ikadarny; Suriah Hanafi, Nur Indah Atifah Anwar, Akbar Yusuf (Adisam Publisher, 2024)
Gross motor development is very important for children. The development of children's gross motor skills requires assistance from educators in educational institutions. The ability to carry out movements and physical actions for a child is related to self-confidence and forming a self-concept. One way to maintain body fitness is through rhythmic exercise. Rhythmic gymnastics are gymnastic movements or free movements accompanied by music that matches the rhythm that follows the movements. Rhythmic gymnastics aims to develop movement abilities, such as developing muscle endurance, strength, flexibility, agility and balance through physical activities, namely playing and exercising which are carried out systematically, directed and planned. Children who are directly involved in rhythmic gymnastics activities will develop flexibility and coordination. To improve a child's gross motor skills, training is needed that is appropriate to the child's characteristics. Gross motor development will be optimal if physical activities are carried out to stimulate it. First, perform coordinated body movements to train flexibility, balance and agility. Second, coordinate the movements of the legs, hands and head in imitating dance or gymnastics. Third, play a physical game with rules. Fourth, be skilled in using your right and left hands. Fifth, carry out personal hygiene activities.